78‐1: The Study of Motion Blur Behavior in the Strobe Backlight LCD for Virtual Reality Application. Issue 1 (2nd June 2017) - Li, Chang-Hung; Lu, Ssu-Hui; Hsieh, Tsung-Ying; Wang, Ko-Shun; Kuo, Wei-Hung; Lee, Ming-Hsien
Abstract : In this paper, we discussed the motion blur behavior relates to MPRT in the strobe backlight LCD for the VR application. The specific equal‐intensity band was observed and was explained by the temporal integration model. After optimizing the flash timing of backlight, less than 4 ms of MPRT was measured in our ultra high resolution LCD.